Awareness of sex and gender dimensions among physicians: the European federation of internal medicine assessment of gender differences in Europe (EFIM-IMAGINE) survey - Biskup Ewelina; Marra Alberto M; Ambrosino Immacolata; Barbagelata Elena; Basili Stefania; de Graaf Jacqueline; Gonzalvez-Gasch Asunción; Kaaja Risto; Karlafti Eleni; Lotan Dor; Kautzky-Willer Alexandra; Perticone Maria; et al. (SPRINGER-VERLAG ITALIA SRL, 2022)
Sociocultural gender is a complex construct encompassing different aspects of individuals' life, whereas sex refers to biological factors. These terms are often misused, although they impact differently on individuals' health. Recognizing the role of sex and gender on health status is fundamental in the pursuit of a personalized medicine. Aim of the current study was to investigate the awareness in approaching clinical and research questions on the impact of sex and gender on health among European internists. Clinicians affiliated with the European Federation of Internal Medicine from 33 countries participated to the study on a voluntary basis between January 1st, 2018 and July 31st, 2019. Internists' awareness and knowledge on sex and gender issues in clinical medicine were measured by an online anonymized 7-item survey. A total of 1323 European internists responded to the survey of which 57% were women, mostly young or middle-aged (78%), and practicing in public general medicine services (74.5%). The majority (79%) recognized that sex and gender are not interchangeable terms, though a wide discrepancy exists on what clinicians think sex and gender concepts incorporate. Biological sex and sociocultural gender were recognized as determinants of health mainly in cardiovascular and autoimmune/rheumatic diseases. Up to 80% of respondents acknowledged the low participation of female individuals in trials and more than 60% the lack of sex-specific clinical guidelines. Internists also express the willingness of getting more knowledge on the impact of sex and gender in cerebrovascular/cognitive and inflammatory bowel diseases. Biological sex and sociocultural gender are factors influencing health and disease. Although awareness and knowledge remain suboptimal across European internists, most acknowledge the underrepresentation of female subjects in trials, the lack of sex-specific guidelines and the need of being more informed on sex and gender-based differences in diseases.